In-situ Preservation Sebagai Strategi Pengelolaan Peninggalan Arkeologi Bawah Air Indonesia - Agni Sesaria Mochtar (KALPATARU, 2016)
Abstract. Indonesia is a renowned country of its richness of underwater archaeological heritage. Abundant maritime cultural activities had provided data to reconstruct the ancient maritime glory. In the matter of fact, the efforts to reconstruct the history are still facing many challenges especially in the lack of main point of view in managing the heritage. Considering that the Indonesian underwater archaeological heritage is of international significance, this paper discusses the opportunity to implement in-situ preservation in managing underwater archaeological heritage in Indonesia, as it is recommended by the 2001 UNESCO Convention. Some issues in the management of underwater cultural heritage, including activities undertaken and related regulation, were discussed through a descriptive approach. This paper then shows that although Indonesia might not ratify the 2001 UNESCO Convention in the near future, in-situ preservation is an ideal strategy to manage the underwater cultural heritage and is applicable in Indonesia, subject to some adjustment of current regulations. Abstrak. Indonesia sangat kaya dengan peninggalan arkeologi bawah air. Berbagai aktivitas budaya maritim telah meninggalkan data yang melimpah untuk merekonstruksi sejarah bangsa ini. Pada kenyataannya, upaya rekonstruksi tersebut masih menghadapi banyak tantangan terutama dalam hal perbedaan sudut pandang pengelolaan tinggalan-tinggalan tersebut oleh para pihak pengelola. Mengingat bahwa peninggalan arkeologi bawah air di Indonesia tidak hanya memiliki signifikansi nasional, tapi juga regional bahkan internasional, kajian ini mengurai kemungkinan penerapan in-situ preservation, sebagaimana tercantum dalam Konvensi UNESCO tahun 2001, sebagai strategi pengelolaan peninggalan arkeologi bawah air Indonesia. Pendekatan deskriptif digunakan untuk menggambarkan permasalahan yang ada dan menunjukkan bahwa meskipun Indonesia belum dapat meratifikasi Konvensi UNESCO tahun 2001 dalam waktu dekat, in-situ preservation merupakan strategi ideal pengelolaan peninggalan arkeologi bawah air yang dapat diterapkan di Indonesia dengan melakukan penyesuaian regulasi yang berlaku.